STRATEGI PROMOSI DIGITAL LIQUID CRACKZ (The Commercium, 2023)
This research aims to find out how the liquid crackz digital promotion strategy is. This research is a qualitative descriptive research with a case study method. The paradigm used is the constructivism paradigm in which social processes are obtained through actions and interactions created by individuals continuously so as to produce a reality that is owned and experinced individually. Data collection was obtained through observation an in-depth interviews. The results of this study indicate that the promotion strategy used by liquid crackz is by utilizing marketing communications with the concept of liquid crackz marketing communication strategies through social media. Social media plays in important role in promoting liquid crackz on instagram